1959
DOI: 10.1111/j.1476-5381.1959.tb00956.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Amine Oxidase and the Central Stimulating Action of the Stereoisomeric Amphetamines and 1‐phenylethylamines

Abstract: The stereoisomers of amphetamine and 1-phenylethylamine have been studied in the rat both as central stimulants and as inhibitors of amine oxidase from brain, liver, and kidney. There was no correlation between these two effects; thus it is unlikely that the central stimulating action of amphetamine is due to inhibition of amine oxidase.It is known that species differences exist in the pattern of substrate and inhibitor specificities Pratesi and Blaschko (1959) showed that, for a substrate as well as for an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1967
1967
1997
1997

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…For example, when tested with the iso lated tracheal muscle preparation of calf, the pD,-values of norepinephrine, and its N methylated (E), ethylated, isopropylated (Iso), and t-butylated analogues were 5.8, 6.7, 7.2, 7.5 and 7.6 respectively (18). It was also reported (22,27) that N,N-dimethylated norepinephrine maintained the adrenergic activity but at a decidedly lower level, and the N,N,N-trimethylated analogue was practically devoid of the activity. Based on these facts, it is generally accepted that the secondary nitrogen atom carrying a bulky sub stituent is essential for the activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when tested with the iso lated tracheal muscle preparation of calf, the pD,-values of norepinephrine, and its N methylated (E), ethylated, isopropylated (Iso), and t-butylated analogues were 5.8, 6.7, 7.2, 7.5 and 7.6 respectively (18). It was also reported (22,27) that N,N-dimethylated norepinephrine maintained the adrenergic activity but at a decidedly lower level, and the N,N,N-trimethylated analogue was practically devoid of the activity. Based on these facts, it is generally accepted that the secondary nitrogen atom carrying a bulky sub stituent is essential for the activity.…”
Section: Discussionmentioning
confidence: 99%
“…The structure-activity relationship of catecholamines, the representative 9-adrenergic stimulants, has been studied for many years by several investigators (11)(12)(13)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Based on the results of these investigations, it is generally accepted that the catecholic hydroxyl groups at position 3 and 4 are essential for manifestation of the Q-adrenergic activity (11-13).…”
Section: Discussionmentioning
confidence: 99%
“…review by BLASCHKO, 1952), a number of studies have confrrmed this finding for a number of species, tissues, and substrates. Thus, preparations from rat, mouse, and rabbit brain (GRANA and LILLA, 1959;GLOWINSKI et al, 1966a;GREEN, 1971;MÖLLER-Nielsen and DUBNIK, 1970;MORGAN et al, 1972b), rat, rabbit, and guinea pigliver (ORzEcHOWSKI, 1941;PRATESland BLASCHKO, 1959;GRANA and LILLA, 1959;FuLLERand WALTERS, 1964;PARMAR, 1966;NIELSEN etal., 1967;YAsUNoBuand 01,1972), rat kidney (GRANA and LILLA, 1959), rat heart (LEITZ and STEFANO, 1971), pig plasma (BUFFONI and DELLA CORTE, 1972), and human brain and salivary glands (BLASCHKO and STRÖMBLAD, 1960) have been used as enzyme sources. Concentrations of amphetamine ranging from 10-5 -10-2 M seem to be needed for inhibition of deamination of typical MAO substrates: adrenaline, noradrenaline, tyramine, oxedrine, kynuramine, benzyl amine, serotonin, tryptamine, and phenylethylamine.…”
Section: D) Enzymatic Inactivation Ofea Oe) Monoamine Oxidase (Mao)mentioning
confidence: 99%
“…It wasconcluded thatcentraleffects of(+)-and (-)-amphetamine, (-)-ephedrine, and (+)-ephedrine possess large indirect components in their activity while those of (+)-pipradrd, (.-)-norephedrine, and (+)-norpseudoephedrine are mainly direct. The effects of the optical isomers of amphetamine were also investigated on brain dopamine levels (305, 306), tissue respiration (307), and liver monoamine oxidase inhibition (284). However, both forms of amphetamine isomers produced similar results, indicating that these effects are not causally related to the central effects.…”
Section: Metabolic Aspectsmentioning
confidence: 99%
“…Although stereochemical substrate specificity was not detected in the early semipurified enzymatic preparations (283)(284)(285)(286), it is now demonstrated that indeed these enzymes do show selectivity for the (-)-isomers of norepinephrine, epinephrine, and rn-octopamine which are better substrates than their corresponding (+)-isomers (287). Kynuramine oxidation by rat liver monoamine oxidase was inhibited more by (+)-isomers (2s) of amphetamine, 2,4-dichloroamphetamine, 4-chloro-N-methylamphetamine, than their corresponding (-)-isomers (288).…”
mentioning
confidence: 99%